THE INFLUENCE OF MANAGERIAL OWNERSHIP AND CAPITAL STRUCTURE ON INCOME SMOOTHING - Tely, Yohana; Wenten, I Ketut (Politeknik Negeri Bengkalis, 2024)
This study aims to analyze the effect of managerial ownership and capital structure on income smoothing. This study uses quantitative methods with secondary data obtained from the annual financial statements of consumer goods industry companies listed on the Indonesia Stock Exchange in 2016-2020. The population used is 52 companies with a research period of 5 years, so that the sample that can be obtained is 14 companies. The analytical method used is the panel data regression analysis method with the estimation of model selection test, model suitability test (Chow test, Hausman test, Lagrange multiplier test), classical assumption test (normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test), test hypothesis and test the coefficient of determination. The program used in this study is Eviews 10. Based on the test, it was found that the variables of managerial ownership and capital structure simultaneously (simultaneously) affect income smoothing or income smoothing. This study also proves that the managerial ownership variable has a significant effect on income smoothing and also that capital structure has a significant effect on income smoothing.